2019
DOI: 10.1002/dc.24187
|View full text |Cite
|
Sign up to set email alerts
|

The Milan system for reporting salivary gland cytopathology: A study of inter‐observer reproducibility

Abstract: Background: In 2018, the Milan System for Reporting Salivary Gland Cytopathology was published defining a diagnostic categorization scheme with known malignancy risks and clinical follow up recommendations. Inter-observer reproducibility of the categories was not defined.Methods: Salivary gland fine-needle aspirations (FNA) were reviewed over a 5 year period and classified by three independent observers. Inter-observer reproducibility was estimated using observed agreement and chance corrected agreement (Cohen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…However, it is well‐known that using the same diagnostic classification scheme does not eliminate observer bias. Several studies have examined the inter‐observer bias related to MSRSGC 13,45,46 . According to these studies, the overall Cohen's kappa score ranged from 0.4 to 0.8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well‐known that using the same diagnostic classification scheme does not eliminate observer bias. Several studies have examined the inter‐observer bias related to MSRSGC 13,45,46 . According to these studies, the overall Cohen's kappa score ranged from 0.4 to 0.8.…”
Section: Discussionmentioning
confidence: 99%
“…Only the studies which separated the NN from the benign neoplastic diagnoses upon histopathological follow‐up were included in calculating the FNA accuracy in detecting neoplasm 11,12,15,17,19,20,22,23,25,26,28,30‐38,40,45 . The studies which solely reported the cytologic‐histopathological correlation among the AUS, SUMP, and/or SM were excluded from the accuracy analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Only with a significant level of interobserver agreement for each of the diagnostic categories can the system succeed in clarifying the meaning of diagnostic terms such as “atypical” and “suspicious for malignancy.” Diagnostic accuracy depends on a variety of factors including clinical features [9, 10] and the skill of the individual obtaining the cytologic material [11, 12]. The impact of the cytopathological interpretation is also of great importance and studies of other categorization systems at other body sites have shown variability in interobserver agreement [13-15]. While the ROM and predictive values for the IAC YSRB have been reported [7, 8, 16], little information is available on the interobserver reproducibility of the 5 categories.…”
Section: Introductionmentioning
confidence: 99%
“…11 et al observed moderate overall agreement with a κ score of 0.42 on 408 salivary gland FNAs. The highest interobserver agreement was noted with the BN category (κ score, 0.71) and the high‐grade M category (κ score, 0.72), whereas the indeterminate categories AUS, SUMP, and SFM had the lowest interobserver agreement with κ scores of 0.15, 0.17, and 0.17, respectively 22 . Finally, before publication of the MSRSGC, the MIRST, a recently published, web‐based interobserver study using a 75‐image study set, was initiated to explore potential cytomorphologic sources of IOV.…”
Section: Discussionmentioning
confidence: 95%